FOREIGN LANGUAGE TEACHERS' PROFESSIONAL QUALIFICATIONS IN SERBIA: REGULATIONS AND PRACTICE (2003 - 2020) (Živi jezici: Journal for Foreign Languages and Literatures, 2020)
This paper offers an analysis of changes and amendments to the rulebook on the education of foreign language teachers in the Serbian education system, created during the first two decades of the 21st century. The research aims to determine - from the perspective of public policy analysis - the dynamics, characteristics, and effects of changes concerning the normative definition of the expertise of foreign language teachers by focusing on the role of various actors. The results of the research show that after 2003, when a major innovation in this area was introduced, the regulations were slightly changed, but that significant changes occurred due to abandonment of examination procedures to ensure and control the quality of staff. By abandoning the mentioned procedures, the possibility of different interpretations of the provisions of the rulebook was opened, and sometimes even placing particular interests above general ones.
Keywords: language education policy in Serbia; public policy; foreign languages; teacher professional qualifications; agents; 2003-2020